Prediction the effect of heat treatment in tensile properties of TI-6AL-4V alloys using artificial neural network - Yan P., Detak; Syarif Junaidi, S Djalil; Rizauddin, Ramli (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.